From Animaculum to single molecules: 300 years of the light microscope. Issue 4 (April 2015) - Wollman, Adam J. M.; Nudd, Richard; Hedlund, Erik G.; Leake, Mark C.
Abstract : Although not laying claim to being the inventor of the light microscope, Antonj van Leeuwenhoek (1632–1723) was arguably the first person to bring this new technological wonder of the age properly to the attention of natural scientists interested in the study of living things (people we might now term 'biologists'). He was a Dutch draper with no formal scientific training. From using magnifying glasses to observe threads in cloth, he went on to develop over 500 simple single lens microscopes (Baker & Leeuwenhoek 1739 Phil. Trans. 41, 503–519. (doi:10.1098/rstl.1739.0085 )) which he used to observe many different biological samples. He communicated his finding to the Royal Society in a series of letters (Leeuwenhoek 1800 The select works of Antony Van Leeuwenhoek, containing his microscopical discoveries in many of the works of nature, vol. 1) including the one republished in this edition of Open Biology . Our review here begins with the work of van Leeuwenhoek before summarizing the key developments over the last ca 300 years, which has seen the light microscope evolve from a simple single lens device of van Leeuwenhoek's day into an instrument capable of observing the dynamics of single biological molecules inside living cells, and to tracking every cell nucleus in the development of whole embryos and plants.